Langerhans cell histiocytosis located in the spheno-orbital bone and the pons: Illustrative case - ÇEKİÇ, EFECAN; KARAGÖZ, AHMET; SAKAR, MUSTAFA; KAÇAR, KADRİYE EBRU; BOZKURT, SÜHEYLA; DAĞÇINAR, ADNAN (My University, 2023)
BACKGROUND This is a case of aggressive Langerhans cell histiocytosis (LCH) with an atypical intracranial location. OBSERVATIONS In this report, the authors present the diagnosis and treatment of a 12-year-old male patient diagnosed with LCH. The patient was admitted to the emergency department with left-sided facial palsy, and a solid lesion with mass effect in the pons was found. A biopsy was performed via suboccipital craniotomy, and the diagnosis was LCH. A chemotherapy regimen was started since the LCH sample was the resistant type. The patient showed improvement in his neurological deficit following treatment. LESSONS This rare localized and aggressive case’s diagnosis process and treatment choices may apply to future cases. https://thejns.org/doi/abs/10.3171/CASE22367.
Keywords: Tıp; Dahili Tıp Bilimleri; Nöroloji; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Neurology; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; KLİNİK NÖROLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; CLINICAL NEUROLOGY; Nöroloji (klinik); Cerrahi; Neurology (clinical); Surgery; brainstem; Langerhans cell histiocytosis; neurosurgery; pediatric oncology; pons; Langerhans cell histiocytosis; brainstem; pons; neurosurgery; pediatric oncology